The reaction of immunophysiological parameters of carp yearlings (Cyprinus carpio) to intraperitoneal administration of Arochlore - Lapirova, T. B. (Regulatory Mechanisms in Biosystems, 2017)
Over 14 days we investigated the effect of a single intraperitoneal administration of Aroclor 1254, one of the most widespread mixtures of polychlorinated biphenyls, on the indexes of the spleen and liver, the level of hemoglobin and the total protein, glucose and circulating immune complexes of the blood serum of carp yearlings (Cyprinus carpio L.). The toxicant was dissolved in vegetable oil, to assess the effect of which the data of a separate group of fish were analyzed in addition to the intact control. It was shown that in both groups of fish injected, both with just oil and with Aroclor dissolved in oil, at the initial stages of the experiment, phase fluctuations of the majority of the investigated parameters were observed, as well as the growth of the individual variability of the indices in comparison with intact individuals. Analysis of the dynamics of change in the obtained data suggests that they are due to the administration of oil which can cause an inflammatory response (handling stress was minimized by anesthesia with MS-222 tricaine methanesulfonate). These changes are generally consistent with the pattern of total nonspecific stress reaction, the manifestations of which are smoothed out by the middle of the exposure. In the experimental group of fish, over these periods pronounced shifts of all indices were again recorded. This phenomenon suggests that during this period the concentration of toxic metabolites formed in the process of transformation of Aroclor reaches values that could significantly shift the homeostasis. This assumption is confirmed by the sharp increase on the 7-th day of the experiment of the content of immune complexes in the bloodstream. Changes by the end of exposure of all biochemical parameters, namely: an increase in the level of glycemia and decrease in the concentration of hemoglobin, serum protein and circulation of immune complexes, were statistically significant. The revealed changes indicate deviations in protein and carbohydrate metabolism and decrease in adaptive potential of fish caused by the toxicant. At the same time, the observed changes are most likely not irreversible and in the absence of further contact with the xenobiotic, the indices can return to normal.